Code of Ethics for Preachers in the Perspective of Surah Surah Thā-Hā Verses 40-46 - Ach. Rifa’i; Akhmad Rifa’i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Many preachers today do not comply with the applicable code of ethics and violate the rules, so that the message of preaching is difficult for listeners to accept. Surah Thā-Hā (Surah 20) from the Qur'an contains very valuable lessons about the code of ethics and procedures for preaching. In verses 40-46, Allah SWT ordered Prophet Musa AS to go to Pharaoh, who was known as one of the unjust rulers of his time. The aim of this research is to find out the code of ethics for preachers contained in Surah Thā-Hā Verses 40-46. The research method used in this research uses qualitative research with a library research approach. The analysis used is content analysis and historical analysis. The data source for this research is primary data in the form of the Koran Surah Thā-Hā Verses 40-46, while the secondary data source is from various related previous writings, both from books and articles that are appropriate to the discussion. The results of this research show that there are several things in the code of ethics contained in Surah Thā-Hā Verses 40-46. The first is brave, the second is patient, the third is gentle, the fourth is always obedient to Allah SWT.